RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY TERHADAP KOMPOSISI BAHAN ORGANIK DAN KONSENTRASI PLANT GROWTH PROMOTING RHIZOBACTERIA - Ety Rosa Setyawati; Gilang Witjaksono (AGROISTA : Jurnal Agroteknologi, 2021)
The objective of this study was to know the effect of plant growth promoting rhizobacteria on organic matter different dosages. This study was conducted in Educational and Research Garden of Instiper at Kalikuning Village, Depok Residence, Sleman, Yogyakarta Province, Indonesia. This study was started at June 18th 2020 until January 2nd 2021. Completely Randomized Design (CRD) was used in this two factorials experiment. The first factor was Plant Growth Promoting Rhizobacteria (PGPR) on 4 levels, those were 0 (control), 5 , 10 and 15 ml/l. The second factor was regusol and organic matter composition. Those were regusol and organic matter composition (1:0), (1:1), and (1:2). Anova was used to analyze if there were any significantly different and then to be continued with Duncan Multiple Range Test at 5 % level. The results of this study showed there were interaction significantly between PGPR consentration with organic matter composition on crown wet weight and crown dry weight. The most efficient was found on 9 ml/l PGPR and 1:1 composition of regusol and organic matter. Key words : pgpr, organic matter, oil palm seedling